2000
DOI: 10.2308/acch.2000.14.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Fraudulent Financial Reporting: Consideration of Industry Traits and Corporate Governance Mechanisms

Abstract: This paper provides insight into financial statement fraud instances investigated during the late 1980s through the 1990s within three volatile industries—technology, health care, and financial services—and highlights important corporate governance differences between fraud companies and no-fraud benchmarks on an industry-by-industry basis. The fraud techniques used vary substantially across industries, with revenue frauds most common in technology companies and asset frauds and misappropriations most common i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
562
6
33

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 929 publications
(722 citation statements)
references
References 7 publications
31
562
6
33
Order By: Relevance
“…Likewise, Abbott, Parker, and Peters (2004) find that ACs consisting of all independent members and with at least one member with accounting or related expertise is negatively associated with financial restatements. Beasley, Carcello, Hermanson, and Lapides (2000) find firms that commit fraud are likely to have less independent ACs. Moreover, Chen and Jaggi (2000) and Erickson et al, (2005) provide a positive relationship between the proportion of independent AC members serving in the board and the comprehensive of financial disclosure.…”
Section: International Journal Of Accounting and Financial Reportingmentioning
confidence: 98%
“…Likewise, Abbott, Parker, and Peters (2004) find that ACs consisting of all independent members and with at least one member with accounting or related expertise is negatively associated with financial restatements. Beasley, Carcello, Hermanson, and Lapides (2000) find firms that commit fraud are likely to have less independent ACs. Moreover, Chen and Jaggi (2000) and Erickson et al, (2005) provide a positive relationship between the proportion of independent AC members serving in the board and the comprehensive of financial disclosure.…”
Section: International Journal Of Accounting and Financial Reportingmentioning
confidence: 98%
“…Between 1997 and 2002, 10 percent of all listed companies restated their financial reports, indicating widespread audit failures (Klein and Coffee 2004). The number of SEC fraud enforcement actions also rose dramatically in this period (Beasley, Carcello, and Hermanson 1999). After a series of major audit failures, including at Enron and WorldCom, public officials grew wary of the auditing profession's ability to maintain proper auditing standards and oversee its members' compliance with such standards.…”
Section: Management's Rolementioning
confidence: 99%
“…Therefore, the audited financial statements comprise a crucial part of the financial reporting system that is required for effective corporate governance. Further, Beasley et al (2000) have suggested the need for auditors to acknowledge weak governance mechanisms that are related to financial fraud across a number of time periods and industries.…”
Section: Introductionmentioning
confidence: 99%